The Funding Burden in Detecting Financial Fraud - Sasongko Tri Utomo; Wisnu Mawardi (Universitas Negeri Semarang, 2023)
The purpose of this research is to analyze the relationship between Leverage, financial performance and earnings manipulation. The Leverage in this study uses a debt to total asset (DART) proxy, while for financial performance it uses a return on asset (ROA) proxy. Manipulation decisions with the beneficial M score model where the results will be seen by companies in the manipulator or non-manipulator category. This study used a sample of manufacturing companies listed on the Indonesia Stock Exchange for the 2016 – 2020 period. The sample was taken using a purposive sampling technique and the number of samples used was 29 companies so the data analyzed was 145 data. The analytical method used is path analysis with SPSS software. These findings indicate that Leverage has a significant negative effect on financial performance. Financial performance has a positive effect on earnings manipulation and financial performance mediates a significant positive relationship between leverage and earnings manipulation. The results of these findings can be used as that for regulators, management, policy makers, government agencies (Financial Services Authority and the Indonesian Stock Exchange) in making procedures or developing a policy that is able to control or closely supervise companies in transparency of the company's financial condition so as to minimize companies committing fraud. financial Manipulation. In addition, this research is still rarely researched because many previous studies have focused on reporting quality, earnings management, financial fraud with proxies other than M Score so that to the author's knowledge no one has researched with a focus on earnings manipulation